Möglichkeiten der Regionalisierung von Wasser- und Stoffhaushaltsuntersuchungen - Cyffka, Bernd; Gerold, Gerhard; Pörtge, Karl-Heinz (ERDKUNDE, 1991)
Regional transfer possibilities of water balance and dissolved load investigations. In the hydrographic research area of Ziegenhagen, the Geographic Institute of the University of Gottingen is trying to record and model the water balance and dissolved load turnover in areal units of varying sizes. The size of these areal units ranges from about 25 m2 over 1.11 km2, 1.37 km2 and 1.76 km2 to the research area size of 14.3 km2.The data prove the transferability of results from small to large catchment areas (upscaling). By using the methods of recording, analysing and modelling for water balance and dissolved load turnover, the items 'water acidification' and 'water quality' are of great importance. For the examination of the water turnover the Geographic Institut is using recorded data from the year 1958 onwards. Data regarding dissolved load turnover from the years 1972 to 1975 are compared with our own measurements of the years 1988 and 1989. The enlargement of the areal unit increases the groundwater-borne portion of discharge as well as the contents of geogenic ions. Further studies with an improved instrumentation will be needed to verify these preliminary results.